Postprandial Lipemic Responses to Various Sources of Saturated and Monounsaturated Fat in Adults - Sciarrillo, Christina M. (Nutrients, 2019)
Background: Postprandial lipemia (PPL) is a cardiovascular disease risk factor. However, the effects of different fat sources on PPL remain unclear. We aimed to determine the postprandial response in triglycerides (TG) to four dietary fat sources in adults. Methods: Participants completed four randomized meal trials. For each meal trial, participants (n = 10; 5M/5F) consumed a high-fat meal (HFM) (13 kcal/kg; 61% of total kcal from fat) with the fat source derived from butter, coconut oil, olive oil, or canola oil. Blood was drawn hourly for 6 h post-meal to quantify PPL. Results: Two-way ANOVA of TG revealed a time effect (p < 0.0001), but no time–meal interaction (p = 0.56), or meal effect (p = 0.35). Meal trials did not differ with regard to TG total (p = 0.33) or incremental (p = 0.14) area-under-the-curve. When stratified by sex and the TG response was averaged across meals, two-way ANOVA revealed a time effect (p < 0.0001), time–group interaction (p = 0.0001), and group effect (p = 0.048), with men exhibiting a greater response than women, although this difference could be attributed to the pronounced difference in BMI between men and women within the sample. Conclusion: In our sample of young adults, postprandial TG responses to a single HFM comprised of different fat sources did not differ.